Retroclival Arachnoid Cysts: Case Series, Literature Review, and New Classification Proposal - ZİYAL, MUSTAFA İBRAHİM (ELSEVIER SCIENCE INC, 2019)
BACKGROUND: The retroclival region is among the rarest locations for an arachnoid cyst (AC), with only a few reported cases. No accepted classification system is available for these rare cysts. Such a classification system would solve the nomenclature problem and could result in easier and more systematic management. We reviewed and analyzed data from databases and reported studies of retroclival ACs (RACs) and have proposed a classification system. METHODS: A retrospective review of RACs was conducted in Marmara and Adiyaman University Hospitals, Turkey. Cysts in the prepontine and/or premedullary cisterns that spared the chiasmatic cistern were included. Additionally, the reported data were searched for relevant studies on cysts. The findings were analyzed to establish a clear nomenclature and classification system, and the clinical presentations, treatment strategies, and surgical approaches were reviewed. RESULTS: We identified 1 adult and 1 pediatric patient, and only the adult had undergone surgery. Additional data searches yielded 14 patients with RACs. The cysts were classified as type 1 if they had extended superiorly beyond the borders of the diencephalic leaf of the Liliequist membrane. If they had not extended, they were classified as type 2. Finally, type 2 cysts that had extended to the anterior spinal cistern were classified as type 3. CONCLUSIONS: RACs can be more easily and systematically managed using a simple clinical classification system. Together with the previously proposed suprasellar AC classification, our proposed RAC classification should be adequate to classify all ACs in the ventral midline cistern, which could solve the nomenclature problem.
Keywords: Arachnoid cyst; Classification; Clivus surgery; Interpeduncular; Prepontine; Retroclival; Suprasellar; ENDOSCOPIC TREATMENT; NATURAL-HISTORY; CHILDREN; PREVALENCE; HEMORRHAGE; MEMBRANE; JUNCTION; ANATOMY; CLIVUS